Modern hindu trinity : Ambedkar-Hedgewar-Gandhi - Bhave, Y. G. (New Delhi, 2005)
Maharshi Aurobindo believed that the 21st century is for the Hindus. Are the Hindus ready for that? Will they rise to the occasion? It will depend on how the Hindu community has shaped itself in the century that has just ended, the 20th century. Three great men have been mainly responsible for moulding the Hindu society in the byegone century, Ambedkar, Hedgewar and Gandhi. They can be definitely referred to as the Modern Hindu Trinity. Ambedkar raised the standard of revolt against the many evils that had crept up in the Hindu society over a period of time and of which untouchability was the worst and most unpardonable sin. Hedgewar diagnosed that the Hindu community of his time lacked vitality in the shape of unity. He advocated that once unity was restored in the Hindu community all its weakness will disappear and it will be ready to face all challenges, both internal and external. Mahatma Gandhi made social reforms in the Hindu society an integral part of the freedom struggle which he led so very ably from 1920 upto the attainment of Freedom. Read this book to understand and appreciate the vital contributions made by these modern Brahma , Vishnu and Mahesh in making the Hindu community ready for its historic role in the current century. You will also be in a position to realise what part you have to play in making Maharshi Aurobindo$1 (Bs prophecy a reality.s
Keywords: India-Politics and government